CRIMINAL ASPECTS OF CHILD VICTIMS OF NARCOTICS CRIME IN THE PERSPECTIVE OF RESTORATIVE JUSTICE - Mailuddin Mabruk, Moh Aziz; Fatoni, Syamsul (JCH (Jurnal Cendekia Hukum), 2023)
Narcotics as a criminal act is often an essential concern in law enforcement cases by the government and society. The purpose of the establishment of the Narcotics Law, as in Article 4, is to prevent, protect and save the Indonesian nation from narcotics abuse and eradicate illicit narcotics trafficking. This research uses normative research methods by examining legislation. This normative research is intended to read legal regulations regarding how the validity of Restorative Justice in protecting children as victims of narcotics crimes. Because there are many cases of minors who are victims in the distribution of narcotics caused by an unstable economy. The regulation of the principle of restorative Justice for children has been accommodated in Indonesian legislation, even in the state constitution, namely the 1945 Constitution of the Republic of Indonesia; it also emphasizes the importance of the position and protection of children's rights, which must be further elaborated in everyday life in the nation and state. Handling children in drug abuse can use alternative efforts with restorative principles that position child punishment as "The Last Resort" with the theory of criminal law as Ultimum remedial, where it can improve itself according to the interests of the child when faced with the law.